On heat exchange - burning conditions relation in manufacturing lime in a rotary kiln - Alexey Alexandrovich Ansimov; Eduard Edgarovich Merker; Alexander Yuryevich Kem (Advanced Engineering Research, 2015)
The work objective is to study the effect of the temperature lime burning conditions in a rotary kiln on the quality indices of the industrial lime used in the steelmaking. The methodology for studying the heat transfer conditions and the temperature behavior of the bulk material under the heat passage and temperature-waves propagation in the semibounded space of a rotary kiln is offered. It is shown that a system of equations describing boundary conditions of the limestone heating by the radiant heat flux becomes increasingly complicated in the case of the parallel convective heat transfer. To simplify the calculations, it is suggested to reduce the combined radiant and convective heat transfer to the convective one (in form) using the known criterial dependences. The investigation results of the heat transfer in the ‘flame - limestone’ system with testing apparent and optimum temperatures in the burning zone are presented. The thermal effect in the rotary kiln on the lime quality indices is specified experimentally under the laboratory and plant conditions. Conditioning of the slag adjustment by the lime consumption during the steel electrosmelting in an arc furnace is defined. Conclusions on the effect of the furnace thermal performance on the principle processes of the carbonate raw materials kilning in the industrial lime manufacturing are formulated. The optimal furnace temperature conditions for manufacturing quality lime with more than 90% CaO are specified.